2020
DOI: 10.1136/jnnp-2020-323331
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of paresis in ALS is consistent with the physiology of the corticomotoneuronal projections to different muscle groups

Abstract: ObjectiveA recent neuroanatomical staging scheme of amyotrophic lateral sclerosis (ALS) indicates that a cortical lesion may spread, as a network disorder, both at the cortical level and via corticofugal tracts, including corticospinal projections providing direct monosynaptic input to α-motoneurons. These projections are involved preferentially and early in ALS. If these findings are clinically relevant, the pattern of paresis in ALS should primarily involve those muscle groups that receive the strongest dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 52 publications
9
30
0
Order By: Relevance
“…Other recent studies have highlighted significant differences in the pattern of weakness in ALS patients which are consistent with the known connectivity of the CSP in humans and non-human primates [ 68 , 69 ]. An example is shown in Figure 1 from a recent study by Ludolph et al [ 68 ], which included both retrospective and prospective studies of a large cohort of ALS patients whose muscle strength was assessed in different pairs of both upper and lower limb muscles, using the MRC scale. The study looked for any statistical sign of asymmetry, in each patient, between pairs of muscle groups, with one group known to receive strong CM connections and the other known to receive weaker connections.…”
Section: The Umn and Amyotrophic Lateral Sclerosissupporting
confidence: 74%
See 1 more Smart Citation
“…Other recent studies have highlighted significant differences in the pattern of weakness in ALS patients which are consistent with the known connectivity of the CSP in humans and non-human primates [ 68 , 69 ]. An example is shown in Figure 1 from a recent study by Ludolph et al [ 68 ], which included both retrospective and prospective studies of a large cohort of ALS patients whose muscle strength was assessed in different pairs of both upper and lower limb muscles, using the MRC scale. The study looked for any statistical sign of asymmetry, in each patient, between pairs of muscle groups, with one group known to receive strong CM connections and the other known to receive weaker connections.…”
Section: The Umn and Amyotrophic Lateral Sclerosissupporting
confidence: 74%
“…Blue bars indicate a difference in the opposite direction. The p -value derived from the sign test of these differences is given at the top of each panel (from Ludolph et al 2020 [ 68 ] Permission obtained).…”
Section: Figurementioning
confidence: 99%
“…These studies support the idea that after CS tract damage, the muscles with the greatest CM influence show greater weakness, and there may be RM involvement in compensatory (rebalancing) mechanisms for motor alterations (Palmer and Ashby, 1992;Belhaj-Saïf and Cheney, 2000;Zaaimi et al, 2012;Ludolph et al, 2020;Sangari and Perez, 2020). In this way, more recently it has been described in Celsr3| Emx1 mutant mice model, where CST is specifically and fully absent, that axonal projections from RN to the spinal cord are increased and lesions of the RS tract lead to defective forelimb use, with almost no recovery.…”
Section: Segmental Neuronal Circuits Modulated By Cs and Rs Systemssupporting
confidence: 79%
“…For example, in patients with amyotrophic lateral sclerosis, a condition that affects the cortex and corticofugal fibers, muscles controlled by α-motoneurons and CM cells are differentially affected. Ludolph et al (2020) compared strength between elbow extensors (triceps) and flexors (biceps), reporting greater relative weakness in flexors relative to elbow extensors; in addition, they also reported greater relative weakness of extensors vs hand flexors. Similarly, in participants with cervical spinal cord damage (tetraplegia) who received transcranial magnetic stimulation, motor-evoked potentials were smaller in triceps relative to controls, suggesting that there is less CS input to the elbow extensors (Sangari and Perez, 2020).…”
Section: Segmental Neuronal Circuits Modulated By Cs and Rs Systemsmentioning
confidence: 99%
“…Although the literature appraising this particular phenomenon is scarce, recent studies emphasised that in upper limbs, the biceps brachii is invariably weaker than of the triceps, irrespective of handedness. [21][22][23] More recently, the presence of the split elbow phenomenon was confirmed in a larger study, although contradictory findings have been reported. 23 24…”
Section: Other Split Phenotypes In the Upper Limbsmentioning
confidence: 90%